Environmental And Social Factors Influencing Elderly’S Subjective Well-Being: Living Arrangement As Moderator - Nainee, Sarvarubini (2024)
The overall population of the elderly is growing worldwide, leading to a silver tsunami whereby the elderly population outweighs the young population. It is not only important to study longevity but also on how people flourish with higher subjective well-being in their later years. This research examines the extent of how physical environmental factors (connectedness to nature and perceived greenness) and social factors (perceived filial piety, perceived social support and generativity) relates to the Malaysian elderly’s subjective well-being. This study also looks at the moderating effect of living arrangements on the relationship between these environmental and social factors and subjective well-being. Participants in this study were 441 elderly living in Ipoh with good cognitive ability and no serious illness. Prescreening procedures were conducted with Short Portable Mental Status Questionnaire to test participants’ mental and cognitive abilities. This study employed a cross-sectional design and a quantitative approach. Data were collected using seven validated self-report questionnaires namely Perceived Greenness Scale, Nature Relatedness Scale, Perceived Filial Piety, Multidimensional Scale of Perceived Social Support,